Visible light induced wetting of nanostructured N-F co-doped titania films - A. G. Kontos; Pelaez, M.; V. Likodimos; Vaenas, N.; Dionysiou, D.D.; P. Falaras (Photochemical and Photobiological Sciences, 2011)
Nitrogen and fluorine co-doped TiO2 films have been prepared by dip coating of a modified titania sol-gel based on a nitrogen precursor and a nonionic fluorosurfactant as pore template and fluorine source. The modified NF-TiO2 films absorb in the visible spectral range, between 400-510 nm and undergo reversible hydrophilic conversion under visible light to a final contact angle of 8°, in contrast to the UV limited optical response of their undoped anatase TiO2 analogues. The phenomenon takes place at a rate slower than the corresponding one observed for the UV stimulated superhydrophilic effect. The wetting response of the N-F doped TiO2 films correlates well with the variation of their optical properties and surface morphological characteristics and most importantly with their photocatalytic activity, rendering these materials very promising for self-cleaning applications under visible light. © 2011 The Royal Society of Chemistry and Owner Societies.
cited By 28